The global integration of business functions: a study of multinational businesses in integrated global industries - Kim, K; Park, J-H; Prescott, J E (Journal of International Business Studies, 2003)
The way that multinational businesses in integrated global industries coordinate and control R&D, manufacturing, and marketing functions across borders has significant implications for performance. We propose that, in such global industries, certain integrating modes will be more effective than others in integrating a function globally. We show that each function has a different combination of effective integrating modes. For global R&D integration, people-based and information-based modes are more effective than formalization-based and centralization-based modes. For manufacturing, people, information, and formalization are more effective than centralization. With respect to marketing, information and centralization are more effective than people and formalization. We also demonstrate that the co-alignment between actual and ideal profiles (configurations or patterns) of integrating modes results in superior performance. Our results reveal that people-based and information-based modes are generally more effective than formalization-based and centralization-based modes in coordinating and controlling business functions worldwide.